Penyuluhan Non Hemoragik Stroke pada Keluarga Pasien di Intensive Care Unit (ICU) RSP. Ibnu Sina YW-UMI - Ernasari, Ernasari; Safruddin, Safruddin; Amir, Haeril; Padhila, Nur Ilah; Suhermi, Suhermi (PT.Mantaya Idea Batara, 2023)
Stroke is a major health problem for society. Almost all over the world, stroke is a serious problem with higher morbidity and mortality rates than cardiovascular disease. A sudden stroke can cause physical and mental disability as well as death, both at productive age and the elderly, 80% of strokes are non-hemorrhagic strokes (NHS). This stroke is caused by many risk factors such as hypertension, cholesterol, obesity, DM, increased hematocrit, according to an initial survey conducted by the service team, we see that patient and family knowledge is still very lacking regarding how to prevent and treat NHS, therefore it is important to hold counseling. This service was carried out in the RSP ICU Room. Ibn Sina YW-UMI. The dedication method is by Lectures/Counseling, Discussions and Questions and Answers. As a result of the dedication, we got the patient's family enthusiastic and active in asking questions so that they are committed to avoiding stress, stopping smoking, exercising, controlling blood pressure, and maintaining a healthy lifestyle, they say their knowledge has increased about stroke.